Occurrence Of Rust Causing Fungus Coleosporium Plumeria On Plumeria Alba In Akola District Of Maharashtra (Journal of Plant Disease Sciences, 2022)
Plumeria is a member of the Apocynaceae family, which includes approximately 300 genera and over 1400 species found primarily in the tropics and subtropics (Dassanayake and Fosberg, 1983). The plant produces a variety of coloured flowers with a pleasant fragrance. It is primarily used for medicinal and religious purposes. The leaves are used as a treatment for cattle wounds. The plant is also used to treat leprosy and fevers (Yadav and Sardesai, 2012). In Maharashtra, they grow as a small ornamental tree in temple pumices, parks, residential areas, and commercial landscapes. Baiswar et al. (2008) first time reported the rust caused by Coleosporium plumeriae on Plumeria alba in Meghalaya state of India in 2008. The disease is also reported in Maharashtra and other parts of country. During the winter, disease severity was at an all-time high. On the lower surface of many leaves, there was a thick layer of bright yellow-orange uredinia. The position of the uredinia was indicated by irregular yellow patches on the upper surface of the leaves. The patches turn dark brown, and the leaves fall prematurely. Other than Plumeria, this rust fungus has no known hosts. Windborne spores and human plant movement spread the disease. Since no research has been conducted on rust infection on Plumeria plants in the Vidarbha region. As a result, a microscopic study for rust infection was carried out, and infected samples were brought to the laboratory for further examination.
Keywords: Plumeria alba; Rust; Coleosporium plumeria; Uridinia